Molecular and Nutritional Review of Phenylketonuria: Implications for Clinical Management - Andre Kristanto (Publikasi Indonesia, 2025)
Phenylketonuria (PKU) is an inborn error of metabolism caused by mutations in the phenylalanine hydroxylase (PAH) gene, which inhibits the conversion of phenylalanine to tyrosine and leads to the accumulation of toxic metabolites. This disorder leads to neurotransmitter deficits, neurological dysfunction, and systemic complications if not addressed early. The primary management of PKU is a lifelong low-phenylalanine diet supported by a phenylalanine-free formula, macronutrient and micronutrient regulation, and pharmacological therapy. Understanding the molecular basis, nutrition, and current therapies is crucial to optimize clinical management and prevent long-term neurodegenerative consequences in individuals with PKU.